Optimización de rutas de vehículos con enfoque multiobjetivo mediante Sistema Basado en Colonia de Hormigas en una Empresa de transporte de Personal - Portella Melchor y Cols., John P. (2018)
This project is aimed at improving route planning by decreasing the total travel distance and the number of vehicles used by a provate transportation company dedicated to driving its corporate clients' staff. This type of companies carries out their route planning process manually and their success is highly dependent on the planner's experience and the know-how of drivers who go along the streets of Lima Metropolitana on a daily basis. These are the main reasons behind the problems related to excessive use of vehicles and the long travel distances to cover. In this context, the proposed solution starts by analyzing the company's planning processes, and then proceed to search for alternative solutions expressed in algorithms that can optimally perform the calculation of the routes. A system based on an ant colony is chosen, then a mathematical model is prepared, and the algorithm is adapted to the conditions of this business. Finally, we implements and test it, adjusting the algorithm's parameters in order to get values that improve the obtained results. The benefits for the company are the reduction in the number of vehicles and the shortening of distances, which in turn results in cost reduction and service quality improvement.